IMPLEMENTASI PERPUSTAKAAN DIGITAL RAMAH DIFABEL (SEBUAH PENGAMATAN PADA PUSTAKA DIGITAL MITRA NETRA) - Atin Istiarni (VISI PUSTAKA: Buletin Jaringan Informasi Antar Perpustakaan, 2019)
The development of library is progressing along with the development of technology. A new era of digitalization becomes a necessity that cannot be avoided by library. Currently, almost all aspects in the library cannot be separated from tachnology and electronic information systems. The conventional systems have been gradually abandoned with the exception of its basic principles of collection management. The development of digital libraries that increases in number proves that there is a paradigm shift about library. The sophistication of technology applied in digital libraries, however, has not met the information accessibility especially for people with disabilities. This paper described the implementation of digital library for the blind throughPustaka Digital Mitra Netra. With the implementation fo digital library for the blind, the right of the blind for information access can be fulfilled. In addition, the concept of digital libraries for the disbled especially the blind can be taken into consideration to be applied in other digital libraries.